2020
DOI: 10.1039/d0ay00889c
|View full text |Cite
|
Sign up to set email alerts
|

A simple and reliable analytical method for simultaneous quantification of first line antitubercular drugs in human plasma by LCMS/MS

Abstract: The present study describes the optimization of a simple and reliable method for the determination of four first line antitubercular drugs in human plasma. The studied analytes were Isoniazid (H),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Our previous study showed that the efficacy of phospholipid removal is more than 95%. 24 Compared with previously published studies, [12][13][14][15][16][17][18][19][20][21][22] our method provides a short analysis time and an efficient clean-up sample procedure which prolongs the column lifetime. The quantification range is enough to quantify selected drugs after their therapeutical doses.…”
Section: Methods Applicationmentioning
confidence: 89%
See 3 more Smart Citations
“…Our previous study showed that the efficacy of phospholipid removal is more than 95%. 24 Compared with previously published studies, [12][13][14][15][16][17][18][19][20][21][22] our method provides a short analysis time and an efficient clean-up sample procedure which prolongs the column lifetime. The quantification range is enough to quantify selected drugs after their therapeutical doses.…”
Section: Methods Applicationmentioning
confidence: 89%
“…Nowadays, the combination of liquid chromatography with tandem mass spectrometry (LC–MS/MS) presents a powerful and sensitive technique to perform TDM on a large number of samples. Several LC–MS/MS methods have been published for simultaneously quantifying anti‐TB drugs in human plasma 12–22 . However, these methods lack good separation and/or peak shape, and suffer from disadvantages like long run time, large sample volume, low sensitivity, and time‐consuming and strenuous sample preparation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasma concentrations were estimated using a simple and validated liquid chromatography-tandem mass spectrometry (LCMS/MS) in the Department of Pharmaceutical Chemistry, Poona College of Pharmacy, Pune, India, developed for simultaneous measurement of all the first-line antitubercular drugs. 5 Suspecting drug-induced polyarthralgia and myopathy, pyrazinamide was discontinued and replaced with levofloxacin 500 mg/d as per NTEP guidelines. 6 Febuxostat dose was increased to 80 mg/d and ibuprofen 400 mg/d for 5 days was added in her drug chart.…”
Section: Case Presentationmentioning
confidence: 99%